2016
DOI: 10.1108/jes-01-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate fluctuations and macroeconomic performance

Abstract: Purpose Recent turbulence in global financial markets implies that emerging economies are likely to soon enter a new era with greater pressure for currency depreciation and capital outflows. This will likely bring challenges, including macroeconomic instability and inflationary pressures due to potential rapid depreciation. In this context, certain key questions about emerging economies have become focal points of discussion in political and academic spheres: what are the effects of exchange rate depreciation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…It also implies that the depreciation of Sterling could bring international competitiveness for the UK's economy and its external balance. The findings are in line with the existing evidence on the presence of J-Curve and response of trade balance to exchange rate dynamics, for instance, study on USA and Indonesia by Bahmani-Oskooee and Harvey (2015) and among others, Bahmani-Oskooee and Hegerty (2010) and Bahmani-Oskooee et al, (2013), Yildirim and Ivrendi (2016). However, the results are contrary to the studies which could not find evidence of a significant impact of exchange rate on the trade balance.…”
Section: Tvsvar Model 43 United Kingdomsupporting
confidence: 91%
See 2 more Smart Citations
“…It also implies that the depreciation of Sterling could bring international competitiveness for the UK's economy and its external balance. The findings are in line with the existing evidence on the presence of J-Curve and response of trade balance to exchange rate dynamics, for instance, study on USA and Indonesia by Bahmani-Oskooee and Harvey (2015) and among others, Bahmani-Oskooee and Hegerty (2010) and Bahmani-Oskooee et al, (2013), Yildirim and Ivrendi (2016). However, the results are contrary to the studies which could not find evidence of a significant impact of exchange rate on the trade balance.…”
Section: Tvsvar Model 43 United Kingdomsupporting
confidence: 91%
“…Similarly, Bahmani-Oskooee (1991) analysis on LDCs reported that devaluation often improves the trade balance in the long run, while in their study on the trade balances of the developed countries, Lane et al ( 2002) reported negative effects of exchange rates appreciation 10 . As the ERPT effects the prices of imports (Ali and Anwar 2016), concomitantly, the improvements in the trade balance are also results of expenditure switching and expenditure changing policies by the household and firms (Yildirim and Ivrendi, 2016). Contrarily, some of the studies focusing on the exchange rate and trade balance could not find a significant link (Rose, 1990) or evidence of J-Curve (Rose and Yellen, 1989).…”
Section: Trade Balance and Erptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, natural disasters also present many risks to the operational environment of a project. In this study, the external environment category comprised of influencing factors such as political stability [48][49][50], financial integration and deepening [52][53][54], global economic climate [51], and natural disasters [55,56].…”
Section: External Environment According Tomentioning
confidence: 99%
“…This process consequently brings new structural problems, namely, liability dollarization and currency mismatch. These problems make the corporations' balance sheets and thereby the default risk more vulnerable to large 6 See Yildirim and Ivrendi (2016) for other theoretical channels through which a currency depreciation influences macroeconomic variables, such as inflation, the money supply, interest rates, investment, and consumption. 7 Anaya and Hasenclever (2018) provide an extensive discussion regarding these two channels.…”
Section: Theoretical Frameworkmentioning
confidence: 99%